Clinical investigation of different types of cases of outdoor patients using ultrasonography in Rangpur Medical College Hospital, Bangladesh (Asian Journal of Medical and Biological Research, 2020)
Ultrasonography is an easy, noninvasive, rapid investigation advised by doctors worldwide. Hence we diagnosed different types of cases through ultrasonography at outdoor patients admitted to Department of Rangpur Medical College Hospital, Rangpur Bangladesh over a period of four months. Our objective was to investigate the prevalence of different types of cases diagnosed and evaluated by ultrasonography in a variety of physical conditions with multiple clinical scenarios. Ultrasonography were performed using GE Logiq V5 Expert ultrasound machine with linear and curved linear phased array transducers. A total 300 cases were diagnosed, where female and male cases were 204 (68%), 96 (32%) respectively. Most ultrasound examinations were abdominal, with the remainder being obstetric, pelvic, breast, and genitourinary examinations. In this study, abdominal ultrasonography represented 118 case (39.33%), Pelvic 54 (18%), KUB 57 (19%), Breast 7 (2.33%) and Obstetrics 64 (21.33%). We found general clinical prevalence of abdominal cases were Cholelithiasis 17 (5.67%), Cholecystitis 3 (1%), Fatty liver 24 (8%), Hepatic Mass 2 (0.67%), Hepatic cyst 1 (0.33%), Acute hepatitis 2 (0.67%), Acute appendicitis 6 (2%), Ascites 2 (0.67%), Hernia 3(1%), Acute pancreatitis 2 (0.67%), Choledocholithiasis 2 (0.67%), Splenomegaly 1 (0.33 %), Abscess 1 (0.33%) and normal cases were 54 (18%). In genitourinary, Stone 20 (6.67%), Cyst 7 (2.33%), RPD 11 (3.67), Cystitis 4 (1.33), Ectopic kidney 1 (0.33%), Enlarged prostate 6 (2%), Hydronephrosis 1 (0.33%), Mass lesion 2 (0.67%) and normal cases were 7 (2.33%). In Pelvic, RPC 11 (3.67%), Ovarian and adnexal cyst 11 (3.67%), Uterine Anomaly 14 (4.67%), Mass lesion 2 (0.67%), Collection 7 (2.33) and normal cases were 5 (1.67%). In Obstetrics, normal pregnancy with no or minor complications, pregnancy with severe complications and abnormal pregnancy were 31(10.33%), 30(10%) and 3(1.0%) respectively. In Breast, dilated duct 1 (0.33%), Abscess 2 (0.67%), Fibroadenoma 2 (0.67%) and normal cases were 2 (0.67%). Here, we found that Fatty liver, stone in genitourinary tract and gall stone were highly prevalent. So, health care providers need to concern and raise awareness to reduce the number of cases.Asian J. Med. Biol. Res. June 2020, 6(2): 294-298